Establishment of an ELISA for detecting oocyst-derived Toxoplasma gondii infections in sheep - Peng, Xinran; Geng, Tiantian; Wang, Yu; Du, Fen; Zhao, Junlong; Fang, Rui; Shen, Bang; Zhou, Yanqin (Frontiers in Veterinary Science, 2026)
BackgroundOvine toxoplasmosis is a zoonotic disease that severely impacts the development of the sheep industry. The primary routes of Toxoplasma gondii infection in sheep are cyst infection and oocyst infection. However, current technologies are unable to distinguish between these two infection pathways.MethodsIn this study, we initially screened eight proteins that are highly specifically expressed during the oocyst stage. Through Western blot (WB) analysis, we identified a protein (TGME49_267410) that could serve as a diagnostic antigen. Subsequently, we optimized the conditions for an indirect enzyme-linked immunosorbent assay (iELISA) using TGME49_267410. Based on these optimized conditions, we collected 1,350 sheep serum samples from various prefecture-level cities in Hubei Province and compared the detection results using both GRA1-iELISA and Tg267410-iELISA.ResultsIn this study, we successfully identified TGME49_267410 as a specific diagnostic antigen for Toxoplasma gondii oocyst-derived infections and established a Tg267410-based indirect enzyme-linked immunosorbent assay (Tg267410-iELISA) for antibody detection. This method exhibited excellent specificity with no cross-reactivity against ovine Haemonchus contortus infections, along with a low limit of detection and good stability of enzyme-linked plates. Serological testing of sheep serum samples from Hubei Province revealed an overall oocyst infection positive rate of 47.4%, where the positive rate in commercial fattening farms (39.9%) was significantly higher than that in breeding sheep farms (12.2%).ConclusionTo summarize, the Tg267410-iELISA established herein enables specific, sensitive, and stable detection of ovine Toxoplasma gondii oocyst-derived infections. This method facilitates the differentiation of infection routes and epidemiological surveillance of ovine toxoplasmosis in Hubei Province and beyond, providing a robust scientific foundation for optimizing targeted prevention and control strategies in sheep farms.